2022
DOI: 10.1186/s12917-022-03496-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, virulence associated genes and phylogenetic background versus plasmid replicon types: the possible associations in avian pathogenic Escherichia coli (APEC)

Abstract: Background Antimicrobial resistance (AMR) in bacterial isolates from food producing animals not only challenges the preventive and therapeutic strategies in veterinary medicine, but also threatens public health. Genetic elements placed on both chromosome and plasmids could be involved in AMR. In the present study, the associations of genomic backbone and plasmids with AMR were evaluated. We also provided some primary evidences that which genetic lineages potentially host certain groups of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(70 reference statements)
0
2
0
2
Order By: Relevance
“…The genomic backbone and plasmid correlations with antimicrobial resistance were investigated [ 43 ]. A total of 72 pathogenic avian E. coli (APEC) strains were studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic backbone and plasmid correlations with antimicrobial resistance were investigated [ 43 ]. A total of 72 pathogenic avian E. coli (APEC) strains were studied.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that group D strains have a high capacity to host a wide range of plasmids (Inc-types) harboring various AMR genes. This means that phylogroup D might pose a problem in dealing with antimicrobial resistance in poultry [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ao redor do mundo não há um padrão único de uso, porém tetraciclinas, macrolídeos, sulfonaminas e aminoglicosídeos estão como os mais descritos(TOHMAZ et al, 2022).Os probióticos são microrganismos ou sua preparação, que atuam com exclusão competitiva na microbiota das aves, ocupando os receptores no intestino, não permitindo a fixação de patógenos, com isso, havendo sua exclusão, além de neutralizar toxinas e estimular o sistema imune. Há alguns microrganismos com esta função, todavia, o Lactobacillus é um dos principais.…”
unclassified
“…relacionadas ao fitness bacteriano, com tendência à disseminação de resistência contra cefalosporinas de terceira geração. O filogrupo B2 não se comporta da mesma maneira, e não há uma correlação entre multirresistência e virulência.Isolados resistentes a Trimetropim-sulfametoxazol, Enrofloxacina, Florfenicol, Neomicina e Furazolidona foram detectados em todos os filogrupos, porém, o filogrupo D foi o que apresentou o maior número de marcadores de resistência(TENAILLON et al, 2010, TOHMAZ et al, 2022. vacinas para Salmonella induziu diferentes graus de anticorpos em galinhas (IgA e IgG), com diminuição de carga bacteriana, lesões e mortalidade(KATHAYAT et al, 2021).Os bacteriófagos são uma alternativa promissora, embora sejam específicos, estão sendo descobertos uma quantidade significativa.…”
unclassified